Parent Coaching dan Aktivitas Berbasis Layar sebagai Bentuk Sedentary Behaviour pada Anak Pra Sekolah - Laviana Nita Ludyanti; Linda Ishariani (Jurnal Sehat Mandiri, 2020)
Screen-based behavior which is part of sedentary behavior arises due to various facilities from the development of science and technology. This has various impacts on growth and development in children, so it is necessary to apply parent coaching. The purpose of this study was to determine the effect of parent coaching on sedentary behavior in pre-school children. This research uses quasy experimental design with a pre testpost test approach. The sample in this study were 45 respondents taken using the Purpossive Sampling Technique. This research was conducted at TK ABA III Pare Kediri. Researchers identified inactivity before and after the parent coaching intervention was given. This study uses a bivariate paired t test analysis. The results of the analysis showed a p value of 0,000 which means that there is an influence between parent coaching on impaired behavior in pre-school children.